Solid state bioconversion of domestic wastewater treatment plant sludge into compost. - Ahmadun, Fakhru'l-Razi (2003)

(untitled)
This invention employs the SSB technique to rejuvenate the composting process as a remedy for safe final disposal and reuse of the DWTP sludge. 8-10% domestic wastewater sludge (from drying bed or LSB) was cured followed by separation of foreign particles and prepared it more or less homogenous. Then it was sterilized after addition of bulking materials (sawdust and rice straw) and optimized the co-substrate, pH, C/N ratio and moisture level.Finally the 6% mixed fungal mixed inocula (approximate 3.5 x 10 spores/ml) was used for inculation and incubated 75 days for bioconversion. T.harzianum with P.chrysosporium 2094 (T/P) and T.harzianum with M.hiemalis (T/M) were found to be the best compatible mixed fungal cultures for the process. Superior composts were produces by T/P around 50-60 days of SSB. This compost could provide 50% N requirement of optimal dose of corn production. 65-100% higher dry matter production was attained by 50% compost plus 50% N treatement.